Optimization of latex production on rubber slow starter clones IRR 42 through application of multiple exploitation system - Murni Sari Rahayu; . Nurhayat (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Rubber is one of the important agricultural commodities. The low production of latex due to the low quality of tapping because the application system of exploitation that does not comply with the clones. Rubber has two groups of clones is a quick starter and a slow starter.This study aims to determine thesystem of exploitation that can increase the production of slow starter clone IRR 42, but still maintain the plant physiological stability. The system exploits tested were tapping system and intervals giving stimulant. The experiment was conducted at the experimental farm of Rubber Research Institute of the White River, covering applications in the treatment field and Physiology Laboratory analysis in the White River Rubber Research Institute, North Sumatera. Thestudytook place fromOktober 2012 toDesember 2012.This researchconducted with randomized block design with two treatments and three replications. Tappingsystem (S) consists of 5 levelsie: S0 = 1/2s d/3.ET 2.5% (control); S1 = 1/4S d / 3.ET 2.5%; S2 = 1/4S d/3.ET 2.5% + 1/2Sd/3; S3 = 1/2s d/3.ET 2.5%; S4 = 1/2s d / 3. ET.2.5% + 1/2Sd/3 and intervalgivingstimulants (W) consists of 2 levelsie W1 = 1 time a month; W2 = 2 times a month.Thesystem of exploitation affect plant physiological conditions, which increase the dryrubbercontent, thecontent of sucrose, lowerthiolcontentresults, and increasethecontent of organic phosphate, but the physiological condition of the plant is still quite normal and does not cause stress in plants. Tapping system that produces the highest production is S4 (1/2s + 1/2Sd/3 d/3.ET.2.5%) and lowest in S1 (1/4S d/3.ET 2.5%). Highest dry rubber content is S4 (1/2s + 1/2Sd/3 d/3.ET.2.5%) and lowest in S1 (1/4S d/3.ET 2.5%.);Highestthiollevels S1 (1/4S d/3.ET 2.5%.) and lowest in S4 (1/2s + 1/2Sd/3 d/3.ET.2.5%); levels of sucrose and organic phosphate levels are highest S4 (1 / 2S + 1/2Sd/3 d/3.ET.2.5%) and lowest in S1 (1/4S d/3.ET 2.5%.). Intervals giving stimulants that produce the highest production is W2 (2 times a month) and lowest in W1 (1 time a month). Highest dry rubber content is W2 (2 times a month) and lowest in W1 (1 time a month); highestlevels of thiolis W1 (1 time a month) and lowest in W2 (2 times a month); levels of sucrose and the highest levels of organic phosphate is W2 (2 times a month) and lowest in W1 (1time a month).